Mapping the anatomic distribution of digital artery perforators: a pilot cadaveric study for reconstructive flap surgery - Rehir, Rasyidah; Dhumale, Sameer (Frontiers in Surgery, 2025)
IntroductionFingertip injuries, particularly crush injuries, are among the most common hand injuries across all age groups. The Digital Artery Perforator (DAP) flap has become a preferred option for fingertip reconstruction due to its simplicity, reliability, and minimally invasive nature compared to techniques like cross-finger or thenar flaps. Despite its growing use, detailed documentation of DAP patterns crucial for effective surgical planning is limited, especially in relation to demographic factors. This study aimed to map the anatomical distribution of DAPs and provide preliminary local data.MethodsSixteen triphalangeal digits (excluding thumbs) from four female cadaveric upper limbs (mean age: 83 years) were injected with gelatin dye and dissected to expose DAPs. Photographs of the dissections were analyzed for DAP distribution across hand laterality, digit type, finger sides, phalanges, and phalanx thirds.ResultsA total of 226 perforators were identified. On average, there were 57 DAPs per hand, 14 per digit, seven per finger side, five per phalanx, and two per phalanx third. Each phalanx contained at least one DAP, with an average of two DAPs per phalanx per finger side.ConclusionHigh-density areas of DAP distribution suggest consistent anatomical patterns, supporting reliable DAP flap design. The findings indicate that preoperative Doppler ultrasound may not be necessary for flap planning, potentially simplifying surgical workflows. While limited by a small sample size, this study offers foundational insights for improving fingertip reconstruction and highlights the need for further research into DAP patterns and their clinical applications.